Leaning to the Left: Increasing the Donor Pool by Using the Left Lobe, Outcomes of the Largest Single-center North American Experience of Left Lobe Adult-to-adult Living Donor Liver Transplantation. Issue 3 (September 2016) - Halazun, Karim J.; Przybyszewski, Eric M.; Griesemer, Adam D.; Cherqui, Daniel; Michelassi, Fabrizio; Guarrera, James V.; Kato, Tomoaki; Brown, Robert S.; Emond, Jean C.; Samstein, Benjamin
Abstract : Objective: Centers offering adult living donor liver transplantation (LDLT) mostly use right lobe grafts due to fears of providing recipients with insufficient hepatic volume, and the technical challenges presented by using left lobe grafts (LLGs). LLGs therefore represent approximately 5% of adult LDLTs performed in the United States. Here we present the largest North American experience with the use of LLG for adult LDLT. Methods: Analysis of a prospectively maintained database of LDLTs performed from 1998 to 2015 at our institution. Results: A total of 214 adult LDLTs were studied. Fifty-six patients (26%) received LLG. LLG recipients were more likely to be women, had significantly lower BMI, graft weight, and graft-weight-recipient-weight ratios ( P < 0.05 for all). There were no significant differences in vascular or biliary complication between the groups. No significant differences existed in patient or graft survival at 1, 3, and 5 years ( P = 0.747 and P = 0.398 respectively). Despite significantly increased risk of small-for-size syndrome in LLG, there was no increased risk of retransplant within 90-days or perioperative mortality in LLG recipients ( P = 0.308 and P = 0.932 respectively). Graft type did not predict patient or graft outcomes on regression analysis ( P = 0.857 and 0.399 respectively). Conclusions: Despite smaller graft sizes, outcomes of adult LDLT using LLG are comparable to right lobe grafts transplants. Left lobes can provide an important resource in an era of severe organ shortages, and these data should serve to allay the concerns of the transplant community in the United States.